Hak Nafkah Istri Dan Anak Yang Dilalaikan Suami Studi Kasus Masyarakat Desa Sanggalima Kecamatan Gebang - Rizkia Farhani (Journal Smart Law, 2023)
The results of the research conducted show that the causes of husbands neglecting their right to provide for their wives and children are due to three main causative factors. The first reason is that her husband has an affair or a third person in his household life. Husbands begin to neglect the right to support their wives and children because they share with their mistresses. Gifts for their children have also decreased considerably and attention to their families has diminished. The second cause is that the husband is involved in drug abuse in the form of drugs, one of which is methamphetamine, which is the common enemy of this nation. The husband has neglected the right to a living for his wife and children because of his involvement in drugs. Many wives have been neglected by their husbands because of the abuse of illegal drugs in the form of narcotics. Husbands no longer give maintenance rights to their wives and children because the money they earn is used up to buy these illicit goods. This is of course very dangerous for the lives of their families and children because it threatens the future of the family, especially their children. It is very important for the family to stay away from these drugs because it will plunge the user into crime. The third problem that causes husbands to neglect their right to support their wives and children is the low income earned by husbands. the factor of the small income of the husband who works as a casual worker is one of the reasons for the small income that his husband gives. Sometimes even sometimes there is no right to provide a living because there is no income. The integrity of the household is very important for the respondent because it maintains the good name of the family. Respondents were also embarrassed when they got divorced because they were classified as old and should have been wiser in fostering a household relationship. Fostering a household must be able to position itself as a wise parent and build a family by setting a good example for their children. She still accepts the right to subsistence that her husband neglected and she is willing to participate in earning a living to meet the needs of her family. The husband's obligations should be fulfilled properly and the key is that the husband must be persistent and enthusiastic in fulfilling a living for his family because that is a worship in the sight of Allah